A Systematic Review of the Association Between Coronary Microvascular Dysfunction and Clinical Outcomes in Heart Failure with Preserved Ejection Fraction - Khairani Putri (The International Journal of Medical Science and Health Research, 2025)
Introduction: Heart failure with preserved ejection fraction (HFpEF) represents a growing global health challenge, characterized by high morbidity and mortality with limited therapeutic options. A contemporary paradigm posits that a systemic inflammatory state, driven by multiple comorbidities, leads to coronary microvascular dysfunction (CMD), a key driver of myocardial pathology in HFpEF. This systematic review aims to synthesize the evidence on the prevalence, pathophysiological correlates, and prognostic significance of CMD in the HFpEF population. Methods: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted to identify observational studies evaluating CMD in patients with HFpEF. Studies were included if they provided data on the prevalence of CMD and/or its association with clinical, echocardiographic, or prognostic outcomes. Data were extracted by two independent reviewers, and the methodological quality of included studies was assessed using the ROBINS-I tool for non-randomized studies. Results: A total of 15 observational studies, enrolling over 2,500 patients, were included. The prevalence of CMD in HFpEF is significantly high, with pooled estimates from meta-analyses ranging from 58% to 71%. The presence of CMD was consistently associated with more severe cardiac pathology, including greater diastolic dysfunction (higher E/e' ratio), increased left atrial volume index (LAVi), and a higher prevalence of atrial fibrillation. Furthermore, CMD was identified as a powerful and independent predictor of adverse clinical outcomes. Multiple studies demonstrated that HFpEF patients with CMD face a substantially higher risk of a composite of all-cause mortality or heart failure hospitalization, with hazard ratios reported to be as high as 3.19. Discussion: The consolidated evidence establishes CMD not as a mere epiphenomenon but as a central, prognostically significant endotype within the heterogeneous HFpEF syndrome. The pathophysiology appears to involve a vicious cycle where systemic inflammation induces CMD, leading to myocardial ischemia and stiffness, which in turn mechanically exacerbates microvascular impairment. The association of CMD with dysfunction in other vascular beds suggests HFpEF may be a manifestation of a systemic microvasculopathy. This understanding positions CMD as a critical target for risk stratification and future therapeutic development. Conclusion: A robust body of evidence establishes CMD as a core component of HFpEF pathophysiology, strongly associated with disease severity and poor prognosis. Assessment of microvascular function holds promise for refining risk stratification in HFpEF, and targeting CMD represents a critical frontier for developing novel, effective therapies for this challenging condition.